Extrações dentárias como tratamento de mutilações labiais em pessoas com deficiência neurológica: relato de caso - Tatibana, Sandy Lais [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Center for the Dental Care for Persons with Intellectual Disabilities (CAOE) assists patients with moderate or severe degree of mental deficiency of diseases or neurological alterations associated or not with mental deficiency that require differentiated dental care. The planning, the need and the opportunity are always analyzed for a multiprofessional team and the complaint and the family history taken into account. Extractions of intact teeth can be performed when restoring oral and overall health depends on such conduct. The objective of this study was to report and discuss cases of people with neurological deficiency who were attended by the CAOE team and who had a habit of mutilation lips, with dental extractions indicated as a form of treatment. Patient NVSR., Female, 7 years old, with cerebral palsy with retarded neuropsychomotor development, gastroesophageal reflux, asthma, unable to walk and talk and with seizures. He had involuntary movements and in 2015 presented great labial mutilation. In the second case, JCO, male, 13 years old, with muscular scoliosis, dislocation of both shoulders, prosthesis in the femur, maxillary locking and epilepsy, fed by a gastric tube, with a full dentition, began to mutilate the lip, causing recurrent hemorrhages . Due to blood aspiration, he was hospitalized more than once even requiring Intensive Care Unit and needed to take antibiotics throughout the year due to recurrent pneumonias. According to the deficiencies presented by the patients, the severity of the injuries caused by the permanence of intact teeth and even the lack or difficulty in creating the technological resources that could provide optional conditions to maintain them led to the difficult decision to indicate radical treatment, as was the case extraction of intact teeth, avoiding the continuity of lip mutilation

O Centro de Assistência Odontológica à Pessoas com Deficiência intelectual (CAOE) assiste pacientes com grau moderado ou grave de deficiência mental de doenças ou alterações neurológicas associadas ou não a deficiência mental que necessitam de atendimento odontológico diferenciado. O planejamento, a necessidade e a oportunidade são sempre analisados de forma multiprofissional e a queixa e o histórico familiar levados em consideração. As extrações de dentes íntegros podem ser executadas quando o restabelecimento da saúde bucal e geral depende de tal conduta. O objetivo deste trabalho foi relatar e discutir casos de pessoas com deficiência neurológica que foram atendidas pela equipe do CAOE e que apresentavam hábito de mutilar os lábios, sendo as extrações dentárias indicadas como forma de tratamento. Paciente NVSR., feminino, 7 anos, portadora de paralisia cerebral com retardo de desenvolvimento neuropsicomotor, refluxo gastroesofágico, asma, impossibilitada de andar e falar e com crises convulsivas. Possuía movimentos involuntários e em 2015 apresentou grande mutilação labial. No segundo caso, JCO, masculino, 13 anos, portador de escoliose muscular, luxação de ambos os ombros, prótese no fêmur, travamento do maxilar e epilepsia, alimentado por sonda gástrica, portador de dentição íntegra, passou a mutilar o lábio gerando hemorragias recorrentes. Devido à aspiração sanguínea, foi internado mais de uma vez, exigindo até de Unidade de Terapia Intensiva e necessitou tomar antibióticos ao longo do ano devido a pneumonias de repetição. Conforme as deficiências apresentadas pelos pacientes, a gravidade das lesões causadas pela permanência de dentes íntegros e até mesmo pela falta ou dificuldade na criação de recursos tecnológicos que poderiam proporcionar condições opcionais para mantê-los levaram...
Keywords: Extração dentária; Automutilação; Crianças com deficiência; Paralisia cerebral; Tooth extraction